PENGARUH KUALITAS LAYANAN ISLAM TERHADAP LOYALITAS NASABAH MELALUI KEPUASAN NASABAH BANK SYARIAH INDONESIA (BSI) CABANG JEMBER - Siti Nurkholisa Apriliany; N. Ari Subagio; Akhmad Munir; Tatok Endhiarto (Study Program of Management Faculty of Economics and Business University of Jember, 2022)
This study was conducted to determine and analyze the effect of Islamic service quality on customer loyalty through customer satisfaction at Bank Syariah Indonesia (BSI) Jember Branch. The analytical technique used in this study is path analysis using SPSS 25 to determine the effect of Islamic service quality variables on customer loyalty through customer satisfaction at Bank Syariah Indonesia (BSI) Jember Branch. The sample used in this study were 140 respondents. Where data acquisition is done through the distribution of questionnaires to customers of Bank Syariah Indonesia (BSI) Jember Branch. The results of this study indicate that the quality of Islamic services has a significant effect on customer satisfaction, customer satisfaction has a significant effect on customer loyalty and the quality of Islamic services has a significant effect on customer loyalty through customer satisfaction at Bank Syariah Indonesia (BSI) Jember Branch.